Electrochemical induced in situ biogas upgrading and nitrogen removal during anaerobic digestion of food waste hydrolysate - Weiyao Huang; Siman Yang; Ze Zhao; Feng Ju; Lei Huang; Meng Li; Hongguo Zhang; Jiaqi Yan; Yunmin Zhong; Xuanxian Liao; Shuyuan Hong; Yue Huang; et al. (Bioresource Technology Reports, 2026)

Emerging Roles of GluN3B NMDA Receptor Subunit in the Central Nervous System - Yuerou Huang; Junyi Xie; Jiamin Chen; Siman Guo; Yuan Li; Fang Liu (Neuroscience Bulletin, 2026)
GluN3B is the most recently identified subunit of N-methyl-d-aspartate receptors (NMDARs), and gradually it has been found that it may be involved in regulating the development of central nervous system (CNS)-related diseases. Compared with the traditional NMDARs containing only GluN1 and GluN2 subunits, non-classical NMDARs with GluN3 have non-conventional biophysical, trafficking, and signaling properties. As a negative regulatory subunit that diminishes or inhibits classical NMDARs' functions, GluN3B plays important roles in synaptic plasticity and neuronal survival, and may be associated with CNS disorders such as schizophrenia and substance use disorders. However, the number and depth of studies on how GluN3B is involved in the regulation of related diseases are very limited. This review summarizes the expression and physiological characterization of GluN3B-NMDARs and provides an overview of their emerging roles in psychiatric and neuropsychiatric disorders, aiming to provide a basis for understanding disease mechanisms and developing novel therapeutic targets.

Dual-templates-assisted synthesis of hollow nanoreactors with hierarchically porous shell for efficient oxygen reduction reaction - Hao Li; Changge Shu; Guo Chen; Ruilian Hu; Erpan Qi; Yiyun Zeng; Siman Zhang; Kang Zhang; Kewen Tang; Kui Shen (Fuel, 2025)

Preparation of Fangxian traditional Xiaoqu and its evolution of microbial communities and aroma compounds during fermentation - Siman Zheng; Mingquan Huang; Wu Yang; Zhongchao Wang; Qing Ren; Hailan Li; Jihong Wu; Nan Meng; Jinchen Li; Bowen Wang (Food Research International, 2025)

Deferoxamine-induced neurotoxicity: Role of chaperone-mediated autophagy dysfunction in neuronal apoptosis in the hippocampus - Hong Zhang; Jian Guo; Jiayi Chu; Huanhuan Yu; Jialin Zhang; Siman Ma; Ge Jin; Yingshan Jiang; Jiao Xiao; Yutong Hou; Minyan Li; Shiliang Yin (Chemico-Biological Interactions, 2025)

Fast prediction of diverse rare ginsenoside contents in Panax ginseng through hyperspectral imaging assisted with the temporal convolutional network-attention mechanism (TCNA) deep learning - Youyou Wang; Siman Wang; Yuwei Yuan; Xiaoyong Li; Ruibin Bai; Xiufu Wan; Tiegui Nan; Jian Yang; Luqi Huang (Food Control, 2024)

Geographical verification of Pleuropterus multiflorus thunb. by functional compounds, stable isotope ratios, and multielement combined with machine learning methods - Feng Xiong; Siman Wang; Chuanzhi Kang; Youyou Wang; Ruibin Bai; Haiyan Li; Jian Yang; Lanping Guo (Food Chemistry, 2024)

Survey of the biogenic amines in typical foods commonly consumed from the Chinese market - Xuan Zhang; Changling Fang; Xiaoyi Lou; Feng Han; Siman Li; Yongfu Shi; Dongmei Huang (Food Control, 2024)

Simultaneous Determination of Seven Pyrethroid Pesticide Residues in Aquatic Products by Gas Chromatography - Changling Fang; Xiaoyi Lou; Xuan Zhang; Siman Li; Yunyu Tang; Yongfu Shi; Dongmei Huang (Fishes, 2024)
Aquatic products are good sources of essential nutrients, but the presence of pyrethroids (PYRs) as contaminants may pose risks to consumer health as the intricate matrices of PYRs usually obstruct chemical hazard detection. In this study, a gas chromatographic method was established and validated for simultaneously detecting residues of seven PYRs (cyhalothrin, permethrin, cyfluthrin, cypermethrin, tau-fluvalinate, fenvalerate, deltamethrin) in aquatic products. The aim of this method was to assess better the potential risks of pesticide residues in aquatic products. The PYRs in aquatic products were extracted with acetonitrile, purified with n-hexane saturated with acetonitrile, and cleaned up on a Cleanert® Alumina N column. Statistical analysis and orthogonal array experimental design were used to optimize the key parameters. To validate the proposed method, commonly consumed aquatic products (such as carp, crucian carp, whiteleg shrimp, river crab, sea cucumber, and scallop) were obtained from local supermarkets in Shanghai. Satisfied linearity of the calibration curves was achieved in a matrix-matched standard solution, with a correlation coefficient (R2) larger than 0.995. The average recoveries at five fortification levels varied from 77.0% to 117.2%, with relative standard deviations (RSDs) below 11.1%. Concerning electron capture detection, the limits of detection (LOD) and limits of quantification (LOQ) were 2.0–5.0 µg/kg and 5.0–10.0 µg/kg, respectively. These results demonstrate the high stability and sensitivity of this method for simultaneously detecting PYRs in aquatic products, having great practicability and which can be popularized easily.

Prediction performance and reliability evaluation of three ginsenosides in Panax ginseng using hyperspectral imaging combined with a novel ensemble chemometric model - Youyou Wang; Siman Wang; Ruibin Bai; Xiaoyong Li; Yuwei Yuan; Tiegui Nan; Chuanzhi Kang; Jian Yang; Luqi Huang (Food Chemistry, 2024)

Characteristics of arsenic speciation in mainly cultured shellfish from Sanmen Bay, Zhejiang Province, China - Maoxia Ran; Yongfu Shi; Di Wu; Hongli Ye; Dongsheng Feng; Dongmei Huang; Siman Li; Changling Fang (Marine Pollution Bulletin, 2023)

Self-assembly of mixed valence polyoxovanadate-based metal-organic frameworks for enhanced CO2 photoreduction - Jilei Wang; Hu Xu; Qin Wang; Jiulin Zhou; Xinying Xiang; Siman Li; Hua Mei; Yan Xu (Chemical Engineering Journal, 2023)

Conversion of swine manure into biochar for soil amendment: Efficacy and underlying mechanism of dissipating antibiotic resistance genes - Yan He; Xin Zhao; Siman Zhu; Long Yuan; Xinyi Li; Zhihan Feng; Xuan Yang; Ling Luo; Yinlong Xiao; Yan Liu; Lilin Wang; Ouping Deng (Science of The Total Environment, 2023)

DRα1-MOG-35-55 treatment reduces lesion volumes and improves neurological deficits after traumatic brain injury - Liu Yang; Zhijia Liu; Honglei Ren; Lei Zhang; Siman Gao; Li Ren; Zhi Chai; Roberto Meza-Romero; Gil Benedek; Arthur A Vandenbark; Halina Offner; Minshu Li (Metabolic Brain Disease, 2017)